PENINGKATAN NILAI KUAT GESER BETON DENGAN MENGGUNAKAN FIBER LOKAL KAWAT BENDRAT BENTUK “U” DAN “Z” DENGAN 3 VARIASI CAMPURAN: indonesia - Juanita Juanita (Universitas Majalengka, 2022)
Concrete is the main basic material used for planning and designing building structures and is widely used as a building material. One of the efforts to improve the unfavorable properties of the concrete in this case is to add bendrat wire fiber to the concrete mix. In this study, bendrat wire fibers in the shape of